Genetically discrete populations of Trypanosoma congolense from livestock on the Kenyan coast - Knowles, G.; Betschart, K.; Kukla, B.A.; Scott, J.R.; Majiwa, Phelix A.O. (Cambridge University Press, 1988)
Twenty-seven stocks of Nannomonas trypanosomes isolated from livestock in 1982 on a ranch at Kilifi on the Kenyan coast were characterized by isoenzyme electrophoresis and by the abilities of the parasite's DNA to hybridize to two repetitive sequence DNA probes. Allthe Kilifi stocks which were examined had isoenzyme patterns which were markedly different from the 75 patterns previously described from 78 stocks of Trypanosoma congolense. On average only 15% of the enzyme bands present in the Kilifi stocks were present in those stocks of T. congolense which had previously been surveyed for isoenzymes. The DNA from all the Kilifi stocks which had been examined for isoenzymes hybridized with only the repetitive sequence probe isolated from a clone of a Kilifi stock. In contrast, the DNA from all 27 Kilifi stocks failed to hybridize with a repetitive sequence probe isolated from a clone from a different stock of T. congolense. Thus, the trypanosomes in all the Kilifi stocks examined were both phenotypically and genotypically discrete. These genetically discrete trypanosomes have also been detected in 2 stocks isolated from livestock from another location on the Kenyan coast. The results show that there is a wide range of genetic heterogeneity within the trypanosomes currently classified as T. congolense. We suggest that the limits of this genetic heterogeneity could represent incipient speciation.